Synonymic Repetitions in the 18th–19th Century Russian Poetry - Синочкина, Б. М. (Kalbotyra, 1981)
The paper is an attempt at the analysis of synonymous collocations that served as one of the necessary language means in Old Russian. Later, owing to the development of the language, the perfection of its lexico-semantic system including, such synonymic word-groups became redundant. Preservation of some of them is mainly due to the conservatism of language and especially to its specific functions in poetry.